Ekonomia w służbie zrównoważonego rozwoju - Anita Ganowicz-Bączyk (Studia Ecologiae et Bioethicae)
The main branch of traditional economics used to focus on economic and social development, and on increasing profits. This led to disregard for the scantiness of natural resources and their renewal. This article looks at the criticism of traditional economic theory by the proponents of the economics of sustainable development, most notable amongst them being the theoretician, Holger Rogall. The notion and crucial principles of the economics of sustainable development are also discussed. The proposed new paradigm in economics is strong sustainability. The theory put forward is strictly related to the idea of sustainable development and the rules of inter- and intragenerational justice and responsibility in the meaning of environmental ethics.